Una “feria masiva” de artes plásticas en el ocaso de la última dictadura argentina - Alejandra Soledad González (Nuevo mundo - Mundos Nuevos, 2016)
In 1983, as the last dictatorship in Argentina was in decline, a new art exhibition in the interior of the country was opened: fair known as Art in Córdoba. A first feature that draws the attention of the exhibition was its massiveness: both Clarín Newspaper and the local press agree that the event involved the movement of a hundred artists, over 1000 works and 6000 attendees as public. Although it took place in the city of Córdoba, it went beyond a local dimension, as several of the artists and summoned works (e.g. Carlos Alonso) remitted to (inter) national contacts that invite to explore networks and appropriations in interprovincial, Latin American and/or European level. This paper proposes a first approach to some edges of these artistic processes from two problem areas: first, the exploration of the possible factors that conditioned the promotion of fair within the official cultural policy and, on the other hand, the description of agents and aesthetic productions that acquired visibility in the context of dictatorial crisis and sociopolitical transition. To begin to untangle some threads of such a complex cultural fabric, our historical reconstruction analyzes a heterogeneous document corpus.